Simplify the expression (3.5x – 2.7y) + (-12.8x + 15.8y)

Question

Simplify the expression (3.5x – 2.7y) + (-12.8x + 15.8y)

in progress 0
Thu Thủy 5 months 2021-09-05T11:08:03+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-09-05T11:09:27+00:00

    Answer:

    -9.3x + 13.1y

    Step-by-step explanation:

    (3.5x – 2.7y) + (-12.8x + 15.8y) = 3.5x – 2.7y – 12.8x + 15.8y =

    = 3.5x – 12.8x – 2.7y + 15.8y = (3.5 – 12.8)x – (2.7 – 15.8)y =

    = -(12.8 – 3.5)x + (15.8 – 2.7)y = -9.3x + 13.1y

    because

    -(-a) = a

    -(a + b) = -a – b

    -(a – b) = -a + b = b – a

    a + (-b) = a – b

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )